Literature Review: Implementation of The Concept of Sustainable Transportation in Soreang Integrated Urban Settlement Areas Planning - Arnesto, Natasha Puteri (UI Scholars Hub, 2025)
Research on sustainable transportation has been growing in recent years to support the Sustainable Development Goals (SDGs). Urban dynamics pose a challenge in achieving these goals, as they are influenced by various factors such as population growth, urbanization, and urban expansion, which occur globally. This trend is also evident in urban areas across Indonesia, including Bandung Regency. Research on sustainable transportation has been growing in recent years as part of efforts to support the Sustainable Development Goals (SDGs). Urban dynamics pose a challenge in achieving these goals, as they are influenced by various factors such as population growth, urbanization, and urban expansion, which occur globally. This trend is also evident in urban areas across Indonesia, including Bandung Regency. Bandung Regency plays a strategic role as a regional buffer zone, providing space for industrial activities, housing, and supporting infrastructure to sustain the capital city of West Java Province. To accommodate this growth, the Bandung Regency Government has developed a Detailed Spatial Plan (RDTR), which includes the development of the Soreang Integrated Urban Area. The increasing intensity of urban activities in Bandung Regency necessitates sustainable spatial management and development policies, particularly in transportation infrastructure provision.